Silicon dioxide modified carbonyl iron powder as well as preparation method and application thereof

A uniform and dense silica shell was prepared on the surface of carbonyl iron powder by means of an improved Stober method, which solved the problems of easy oxidation and poor corrosion resistance of carbonyl iron powder and achieved high-performance anti-corrosion effect in epoxy resin coating.

CN121086552APending Publication Date: 2025-12-09JIANGXI COLLEGE OF APPLIED TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511443624.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-10
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

Carbonyl iron powder is easily oxidized, has poor corrosion resistance, and exhibits poor dispersibility and interfacial bonding in epoxy resin coatings. Existing coating methods result in uneven and non-dense coating layers, making it difficult to provide effective protection in high-temperature environments.

Method used

By employing the improved Stober method, a uniform and dense silica shell is prepared on the surface of carbonyl iron powder through precise control of the amount of ammonia catalyst and the hydrolysis temperature and time of tetraethyl orthosilicate. This forms a core-shell structure of silica-modified carbonyl iron powder, which is then combined with an epoxy resin matrix to prepare an anti-corrosion composite coating.

Benefits of technology

It significantly improves the oxidation resistance and corrosion resistance of carbonyl iron powder, enhances the density and adhesion of the coating, extends the service life of the composite coating, increases the low-frequency impedance modulus, and reduces the corrosion current density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121086552A_ABST
    Figure CN121086552A_ABST
Patent Text Reader

Abstract

The invention discloses silicon dioxide modified carbonyl iron powder as well as a preparation method and application thereof. According to the modified material, micron-sized carbonyl iron powder serves as a core, the surface of the modified material is coated with a nano-sized silicon dioxide layer through an improved Stober method, a core-shell structure is formed, the thermal stability and corrosion resistance of the carbonyl iron powder are remarkably improved, and the initial oxidation temperature of the carbonyl iron powder is not lower than 300 DEG C and is increased by at least 50 DEG C compared with an unmodified product. The preparation method comprises the steps of dispersion, mixed catalysis, coating reaction and post-treatment, and is simple in process and high in controllability. The invention further provides application of the modified carbonyl iron powder in an epoxy resin-based anticorrosive coating, when the filling amount is 0.1-2.0% (preferably 1.00%), the coating shows excellent anticorrosive performance in a 3.5 wt% NaCl solution, the low-frequency impedance modulus value is not lower than 7.0 * 10 < 5 > omega.cm < 2 >, and the corrosion current density is not higher than 2.15 * 10 <-8 > A / cm < 2 >. The method effectively solves the problems that the carbonyl iron powder is easy to oxidize and agglomerate and poor in corrosion resistance, and is suitable for the high-performance anti-corrosion and wave-absorbing integrated coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of materials science and corrosion protection technology, specifically relating to a silica-modified carbonyl iron powder (CIP@SiO) and its preparation method, as well as the application of this modified material in epoxy resin-based anti-corrosion composite coatings. Background Technology

[0002] Carbonyl iron powder (CIP), as a typical magnetic metallic microwave absorbing material, exhibits broad application prospects in radar stealth, electromagnetic shielding, engine components, and aircraft stealth technology due to its excellent properties such as high magnetic permeability, moderate electrical conductivity, low coercivity, and a Curie temperature as high as 770℃. Its absorption mechanism mainly stems from magnetic loss, which converts the energy of incident electromagnetic waves into heat or other forms of energy dissipation.

[0003] However, the widespread application of carbonyl iron powder is severely limited by its inherent drawbacks. Firstly, carbonyl iron powder is chemically reactive and has a large specific surface area. When exposed to air for extended periods, especially under high temperature, high humidity, or corrosive media (such as Cl), it becomes susceptible to adverse effects. - In environments with high humidity and humidity, carbonyl iron powder is highly susceptible to oxidation and corrosion, leading to a significant decrease in its magnetic properties and a sharp decline in its wave absorption efficiency. For example, the blackening of magnetic jewelry worn in daily life due to oxidation is a direct manifestation of the instability of carbonyl iron powder. Secondly, carbonyl iron powder particles are prone to agglomeration due to magnetic attraction and other factors, which not only affects its dispersion in the matrix material but also limits the performance optimization of its composite materials.

[0004] To improve the durability of carbonyl iron powder, researchers have explored various surface modification methods. Among these, constructing a core-shell structure is considered an effective strategy, which involves coating the carbonyl iron powder core with a chemically stable material to isolate it from the external environment. Currently, common surface modification methods mainly include organic and inorganic coatings. While organic coatings (such as polyamides and polypyrroles) can improve corrosion resistance to some extent, their high-temperature resistance is generally poor, and they are prone to decomposition and failure at high temperatures, making it difficult to meet the application requirements of microwave absorbing materials under high-temperature conditions. Among inorganic coatings, silica (SiO2) has attracted widespread attention due to its excellent chemical stability, heat resistance, low electrical conductivity, and ease of controllable coating via the sol-gel method.

[0005] Although there are reports of using the Stober method to coat SiO2 onto the surface of carbonyl iron powder, these methods still have some unresolved issues. For example, due to the smooth surface of carbonyl iron powder, the hydrolysis and condensation process of SiO2 precursors (such as tetraethyl orthosilicate, TEOS) on its surface is difficult to control, often resulting in uneven and non-dense coatings, or even localized exposure or SiO2 agglomeration. Such defective coatings are unlikely to provide long-term and effective protection for carbonyl iron powder under harsh environments, and their effect on improving oxidation and corrosion resistance is limited. Furthermore, how to effectively composite modified carbonyl iron powder with a polymer matrix (such as epoxy resin) to prepare a composite coating with both excellent microwave absorption properties and long-term anti-corrosion function, and how to systematically optimize and quantitatively characterize the coating process and the performance of the composite coating, remain current research challenges.

[0006] Therefore, developing a modified carbonyl iron powder with a uniform, dense, and firmly bonded silica shell that can significantly improve the oxidation resistance and corrosion resistance of carbonyl iron powder, and thus be suitable for high-performance epoxy resin anti-corrosion composite coatings, as well as its controllable preparation method, has important practical significance and application value. Summary of the Invention

[0007] To address the problems of easy oxidation, poor corrosion resistance, and poor dispersibility and interfacial bonding of carbonyl iron powder in epoxy resin coatings mentioned in the background art, this invention discloses a silica-modified carbonyl iron powder, its preparation method, and its applications. This core-shell structured powder exhibits significantly improved thermal stability, oxidation resistance, and corrosion resistance, effectively extending the service life of composite coatings and broadening their application environments. The preparation method described in this invention, based on the design concept of constructing a dense and uniform silica insulating protective layer, employs a modified Stober method. By precisely controlling key process parameters such as the amount of ammonia catalyst and the hydrolysis temperature and time of tetraethyl orthosilicate, a complete and firmly bonded SiO2 shell layer is successfully prepared on the surface of micron-sized carbonyl iron powder, providing a reliable material basis for its application in high-performance anti-corrosion and microwave absorption integrated epoxy resin coatings.

[0008] To achieve the above objectives, the present invention includes the following technical solutions: A silica-modified carbonyl iron powder, wherein the carbonyl iron powder forms the core, and its surface is coated with a silica layer to form a core-shell structure; the silica layer is formed by hydrolysis and condensation on the surface of the carbonyl iron powder using a modified Stober method with tetraethyl orthosilicate as the silicon source under ammonia catalysis; the presence of the silica layer ensures that the initial oxidation temperature of the modified carbonyl iron powder is not lower than 300°C, which is at least 50°C higher than that of unmodified carbonyl iron powder.

[0009] Furthermore, the carbonyl iron powder modified with silica described above has a particle size range of 1~6μm.

[0010] Furthermore, in the aforementioned silica-modified carbonyl iron powder, the thickness of the silica layer is at the nanometer level, and the surface roughness of the carbonyl iron powder is significantly increased after coating.

[0011] The preparation method of the above-mentioned silica-modified carbonyl iron powder includes the following steps: (1) Dispersion: Weigh 8 parts by weight of carbonyl iron powder and add it to 160-200 parts by volume of deionized water to form a preliminary suspension; (2) Mixed catalysis: Mix 1 volume part of ammonia water with 40-60 volume parts of anhydrous ethanol to obtain a catalytic solution; mix the catalytic solution with the preliminary suspension from step (1), and treat with ultrasonic vibration for 5-15 minutes to obtain a uniformly dispersed carbonyl iron powder suspension. (3) Coating reaction: Place the suspension obtained in step (2) in a constant temperature water bath at 35±2℃, and slowly add 4-6 volume parts of tetraethyl orthosilicate under continuous stirring. Control the stirring rate to 250-300 r / min and the reaction time to 3-4 hours. (4) Post-processing: After the reaction is completed, the reaction product is vacuum filtered to achieve solid-liquid separation, and the obtained solid product is washed 3-5 times alternately with deionized water and anhydrous ethanol; finally, the washed product is dried in a vacuum drying oven at 75-85℃ for 2-3 hours to obtain the silica-modified carbonyl iron powder.

[0012] Furthermore, in the above preparation method, the ultrasonic oscillation time in step (2) is 10 minutes.

[0013] Furthermore, in the above preparation method, the amount of tetraethyl orthosilicate added in step (3) is 5 parts by volume.

[0014] The present invention also discloses an anti-corrosion composite coating, which is composed of an epoxy resin matrix and carbonyl iron powder modified with silica as described in any one of claims 1-3 dispersed therein.

[0015] Furthermore, in the aforementioned anti-corrosion composite coating, the silica-modified carbonyl iron powder has a mass percentage of 0.1% to 2.0% in the epoxy resin matrix.

[0016] Furthermore, in the aforementioned anti-corrosion composite coating, the silica-modified carbonyl iron powder accounts for 1.00% of the mass percentage of the epoxy resin matrix; the low-frequency impedance modulus of this coating in a 3.5 wt.% NaCl solution is not less than 7.0 × 10⁻⁶. 5 Ω·cm 2 The corrosion current density is not higher than 2.15 × 10⁻⁶. -8 A / cm 2 .

[0017] This invention also discloses a method for preparing the above-mentioned anti-corrosion composite coating, comprising the following steps: Mix the specified mass percentage of silica-modified carbonyl iron powder with epoxy resin A, and disperse it for 15-25 minutes at a rate of 10000-15000 r / min using an ultrasonic disperser. Add the appropriate proportion of epoxy resin B glue, and mechanically stir for 10-20 minutes to make the mixture uniform; Place the mixture in a vacuum environment to remove air bubbles for 5-15 minutes; The degassed mixture is coated onto the surface of the pretreated metal substrate and cured at room temperature for no less than 12 hours to form the anti-corrosion composite coating.

[0018] Compared with the prior art, the present invention has the following outstanding advantages: This invention significantly improves the oxidation and corrosion resistance of carbonyl iron powder through silica coating modification. The core-shell structure effectively isolates the carbonyl iron powder from external corrosive media, delaying oxidation and electrochemical corrosion processes. The modified powder's initial oxidation temperature increases to over 300℃, enhancing thermal stability. It exhibits uniform dispersion and tight interfacial bonding in the epoxy resin coating, improving coating density and adhesion. The composite coating demonstrates excellent barrier properties and corrosion resistance, significantly improving the low-frequency impedance modulus and reducing corrosion current density, thus extending the service life of the metal substrate. This invention offers good process repeatability and environmental friendliness, providing a reliable material basis for the application of carbonyl iron powder in harsh environments. Attached Figure Description

[0019] Figure 1 Preparation process of silica-coated carbonyl iron powder (CIP@SiO2); Figure 2 Preparation process of anti-corrosion coating composed of CIP@SiO and epoxy resin; Figure 3 Thermogravimetric analysis (TGA) diagrams of carbonyl iron powder before and after modification; Figure 4 Open circuit potential diagrams of carbonyl iron powder before and after modification; Figure 5 Impedance spectra of carbon-based iron powder before and after modification; Figure 6 Polarization curves of carbonyl iron powder before and after modification; Figure 7 Scanning electron microscope images before and after modification: (a) CIP; (b) CIP@SiO2; Figure 8 CIP@SiO2 energy dispersive spectroscopy results: (a) elemental energy spectrum; (b) Fe element; (c) Si element; (d) C element; (e) O element; Figure 9 Cross-sectional morphology (a) 5000x CIP@SiO2; (b) 2000x CIP@SiO2; Figure 10 Open circuit potential diagrams of carbonyl iron powder / epoxy resin coating before and after modification; Figure 11 Impedance spectra of carbonyl iron powder / epoxy resin coating before and after modification; Figure 12 Polarization curves of carbonyl iron powder / epoxy resin coating before and after modification. Detailed Implementation

[0020] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] The reagents used in the examples are shown in Table 1, and the equipment is shown in Table 2.

[0022] List of drug test materials, specifications, and manufacturers. ; Table 2. Names, Models, and Manufacturers of Experimental Instruments ; Example 1: The preparation of silica-coated carbonyl iron powder (CIP@SiO2), such as Figure 1 The process, as shown, includes the following steps: 1) Dispersion: Accurately weigh 8.0 g of carbonyl iron powder with a particle size of 1-6 μm and add it to a 250 ml beaker containing 160 ml of deionized water.

[0023] 2) Mixed catalysis: Measure 1 mL of analytical grade ammonia and 40 mL of anhydrous ethanol and mix them thoroughly in another beaker to obtain a catalytic solution. Pour this catalytic solution into the carbonyl iron powder suspension from step 1.

[0024] 3) Ultrasonic dispersion: Place the above mixture in a CNC ultrasonic cleaner and ultrasonically treat it for 10 minutes at a power of 250W to fully and evenly disperse the carbonyl iron powder.

[0025] 4) Coating reaction: The ultrasonicated mixed suspension was transferred to a constant temperature water bath at 35°C, and the electric stirrer was turned on and stirred continuously at a rate of 270 r / min. Then, 5 mL of analytical grade tetraethyl orthosilicate (TEOS) was slowly added dropwise using a dropper. After the addition was complete, the reaction was continued at a constant temperature and stirred for 3 hours.

[0026] 5) Post-processing: After the reaction is complete, the reaction product is filtered using a circulating water vacuum pump to achieve solid-liquid separation. The filter cake is washed four times alternately with deionized water and anhydrous ethanol to remove residual ammonia and byproducts. The washed solid product is then transferred to a vacuum drying oven and dried at 80°C for 3 hours.

[0027] 6) Obtaining the product: After drying, a black powder product is obtained, which is silicon dioxide modified carbonyl iron powder (CIP@SiO).

[0028] Example 2: An anti-corrosion coating composed of CIP@SiO2 and epoxy resin prepared in Example 1 and its preparation method are disclosed. Taking a coating where the CIP@SiO2 filler content is 1.00% of the epoxy resin mass as an example, ... Figure 2 The process, as shown, includes the following steps: 1) Substrate pretreatment: Take a standard metal sheet (Q235 steel), polish its surface with sandpaper until smooth, rinse it with anhydrous ethanol, place it in an ultrasonic cleaner for 5 minutes, take it out and let it air dry for later use.

[0029] 2) Mixing: Accurately weigh 1.00% of the total mass of epoxy resin prepared in Example 1 and add it to epoxy resin A (E44 type).

[0030] 3) Dispersion: Place the mixture in an ultrasonic disperser and disperse it at a rate of 13000 r / min for 20 minutes to ensure that CIP@SiO2 is evenly distributed in the resin.

[0031] 4) Curing: Add the appropriate proportion of epoxy resin B glue (type 650) to the above mixture and stir with a mechanical stirrer for 15 minutes to ensure thorough and uniform mixing.

[0032] 5) Degassing: Place the well-mixed slurry into a vacuum drying oven and vacuum for 10 minutes to eliminate air bubbles introduced during the mixing process.

[0033] 6) Coating and molding: Using a 50μm wire bar coater, the degassed slurry is uniformly coated onto the surface of the pretreated metal sheet. Subsequently, the coated metal sheet is placed at room temperature for pre-curing for 12 hours to form the final CIP@SiO-1.00% / epoxy resin composite coating.

[0034] Composite coatings with CIP@SiO filling amounts of 0.50% and 0.75% were prepared using the same method, as well as composite coatings with unmodified CIP filling amounts of 0.50%, 0.75%, and 1.00% as comparative examples.

[0035] Test example: Performance characterization of modified carbonyl iron powder and its composite coating: Test method: 1) Microscopic morphology and phase analysis: Scanning electron microscopy (SEM) is a microscopic analytical instrument with electronic properties, commonly used to observe the microscopic morphology and structure of sample surfaces. It utilizes a focused electron beam to scan the sample surface, generating backscattered and secondary electrons to depict the surface morphology of the material. This paper uses SEM to compare and analyze the microscopic morphology of carbonyl iron powder before and after modification, determining whether the modified carbonyl iron powder surface is uniformly and completely coated with silica.

[0036] Energy dispersive spectroscopy (EDS) is an instrument that analyzes the energy distribution of matter. It analyzes the structural elements and their abundance by detecting signals generated by the interaction between matter and incident particles. It is typically used in conjunction with scanning electron microscopy to analyze microscopic morphology and elemental distribution.

[0037] 2) Thermogravimetric analysis: The thermal stability of the prepared CIP and CIP@SiO2 composite materials was analyzed using a thermogravimetric analyzer (Netzsch, Germany, model STA449F3). Approximately 3-5 mg of sample was taken for each test. Under atmospheric protection, the temperature was increased at a rate of 15 °C / min, ranging from 25 °C to 800 °C. The changes in the oxidation weight gain of carbonyl iron powder before and after modification with increasing temperature were analyzed.

[0038] 3) Electrochemical analysis: This experiment used a Chenhua (CHI660E) electrochemical workstation. The thermal stability, corrosion, and oxidation properties of the materials were analyzed by measuring parameters such as electrode potential and current density. It can perform electrochemical analysis methods such as cyclic voltammetry, differential pulse voltammetry, linear sweep voltammetry, and chronoamperometry. The electrochemical corrosion tests used in this experiment mainly included open-circuit potential (OCP), impedance spectroscopy (EIS), and polarization curve analysis. A three-electrode electrolytic cell system was used. The counter electrode was a platinum sheet electrode, the reference electrode was a saturated calomel electrode (SCE), and the working electrode was the coating to be tested. All electrodes were circles with an inner diameter of 0.5 cm. The sample was uniformly pressed onto the electrode and immersed in a 3.5 wt.% NaCl electrolyte solution at room temperature. The open-circuit potential (OCP) was measured when the potential value stabilized at 0.5 mV / min, with a total time of 600 s and an interval of 0.1 s, within the range of 0.1 V to -0.6 V. The electrochemical impedance spectroscopy (EIS) frequency range was 10... -2 ~10 -5 The Hz value represents the AC potential amplitude of 10mV. The potential of the potentiodynamic polarization curve is referenced to the open-circuit potential, and the scan rate is 5mV / s.

[0039] Test results: 1) Performance analysis of carbonyl iron powder before and after modification: Antioxidant performance test.

[0040] Figure 3 The thermogravimetric analysis (TGA) results are shown before and after SiO2 coating of carbonyl iron powder. The sample was placed in an air atmosphere and heated from 25°C to 800°C at a rate of 10°C / min. Figure 3 The results show that, under air conditions, unmodified carbonyl iron powder begins to oxidize and gain weight at around 200℃, and is completely oxidized after 550℃. The original carbonyl iron powder shows a faster weight gain rate between 450 and 500℃, while the SiO2-coated carbonyl iron powder only begins to show weight gain at 300℃, with the weight gain rate accelerating between 500 and 600℃, and is completely oxidized after 600℃. This is because the SiO2 coating layer is damaged at high temperatures, causing the carbonyl iron powder to oxidize and gain weight when exposed to air. Thermogravimetric analysis shows that the modified carbonyl iron powder has a reduced contact area with oxygen and exhibits better oxidation resistance than the original carbonyl iron powder; however, at temperatures above 550℃, the silica coating layer still cannot provide sufficient oxidation resistance.

[0041] 2) Electrochemical analysis of carbonyl iron powder before and after modification: open circuit potential diagram analysis.

[0042] like Figure 4 This diagram shows the open-circuit potential of carbonyl iron powder and silica-coated carbonyl iron powder. 5 mL represents the amount of tetraethyl orthosilicate added. Tests were conducted within the range of -0.6 V to -0.44 V for a total duration of 600 s. The magnitude of the open-circuit potential reflects the corrosion resistance of the carbonyl iron powder before and after modification. The potential of sample CIP was -0.50 V, and the potential of CIP@SiO2-5 mL was -0.56 V. The SiO2 coating on the CIP surface isolates the iron powder from contact with the outside air, slowing down the corrosion process. Over time, the modified carbonyl iron powder exhibits a higher open-circuit potential and superior corrosion resistance.

[0043] 3) Electrochemical analysis of carbonyl iron powder before and after modification: impedance spectroscopy analysis.

[0044] like Figure 5 Electrochemical impedance spectroscopy (EIS) spectra of carbonyl iron powder before and after modification. Figure 5 In the diagram, (a) and (b) are the Nyquist plot and Bode plot, respectively. In the Nyquist plot, the shape of the impedance spectrum arc indicates the corrosion resistance; a larger arc indicates stronger corrosion resistance. Figure 5 As shown in (a), the impedance spectrum radian of CIP is significantly smaller, while the impedance spectrum radian of CIP@SiO2-5mL is significantly larger than that of CIP. This indicates that the silica coating on the carbonyl iron powder surface effectively improves the oxidation resistance, enhances the corrosion resistance, and reduces the corrosion rate.

[0045] Depend on Figure 5 As shown in (b), the resistivity modulus |Z| in the low-frequency region is generally used to analyze the corrosion resistance of the sample. The impedance value of the carbonyl iron powder sample and the Bode plot at 0.01 Hz in the low-frequency region is 2.5 × 10⁻⁶. 4 Ω·cm 2 The Bode plot impedance of CIP@SiO2-5mL at 0.01Hz in the low-frequency region is 1.3 × 10⁻⁶. 5 Ω·cm 2 The impedance value is increased by 1.1 × 10 compared to the CIP sample. 5 Ω·cm 2 This indicates that the modified carbonyl iron powder has a higher resistivity modulus and significantly improved corrosion resistance and oxidation resistance.

[0046] 4) Electrochemical analysis of carbonyl iron powder before and after modification: polarization curve analysis.

[0047] like Figure 6 Table 3 shows the polarization curves of carbonyl iron powder before and after modification. Table 3 presents the results after fitting the polarization curves. Corrosion potential (E) corr E is a thermodynamic parameter. corr The value is related to the corrosion performance of the sample, E corr The smaller the value, the more susceptible the sample is to corrosion. Current density (I corr I is an important parameter characterizing the corrosion resistance and corrosion rate of a material. corr A smaller value indicates a lower corrosion rate and therefore stronger corrosion resistance. The E value of the CIP sample... corr The value is -0.736V (SCE), E of CIP@SiO2-5mL corr The value is -0.535V (SCE), which is -0.201V (SCE) higher than that of uncoated carbonyl iron powder, making it less susceptible to corrosion. CIP's I corr The value is 1.3410 -6 A / cm 2 CIP@SiO2-5mL of I corr The value is 1.7810 -7 A / cm 2 The modified carbonyl iron powder exhibits a lower current density than the unmodified powder, with a corrosion potential difference of 1.1610. -6 A / cm 2 Experimental results show that carbonyl iron powder coated with silica has superior corrosion resistance compared to uncoated powder.

[0048] ; Table 3. Results of sample polarization curve fitting In summary, SiO2 exhibits excellent chemical stability and forms a dense protective film on the CIP surface, preventing contact between corrosive substances and iron powder and slowing down the corrosion rate.

[0049] 5) Analysis of carbonyl iron powder / epoxy resin coating before and after modification: SEM morphology analysis.

[0050] like Figure 7 These are scanning electron microscope (SEM) images of raw carbonyl iron powder and SiO2-coated carbonyl iron powder. Figure 7 As observed in (a, b), the carbonyl iron powder particles have a uniform size ranging from 1 to 6 μm, and the original carbonyl iron powder microspheres have a relatively smooth surface. After surface coating the original carbonyl iron powder with SiO2 using the modified Stober method, the individual particles on the surface become rougher, but the change in microstructure is not significant compared to the unmodified carbonyl iron powder. This is because the original carbonyl iron surface is smooth, and the SiO2 produced by the hydrolysis of tetraethyl orthosilicate is difficult to precipitate uniformly on the surface of the carbonyl iron powder during stirring, resulting in a thinner surface coating and poorer thermal insulation. At high temperatures, it is difficult to prevent air from contacting the original carbonyl iron powder, which may directly damage the SiO2 coating. The SiO2 coating can improve the impedance matching and microwave absorption performance of carbonyl iron powder.

[0051] To ensure successful silica coating, EDS was used to characterize the phase composition of the samples. Figure 8 As shown in the energy dispersive spectroscopy (EDS) spectrum, the main elements in CIP@SiO2 are Fe, O, C, and Si, with mass percentages of 87.68%, 0.58%, 0.87%, and 0.68%, respectively. Although the mass percentages of Si and O are relatively small, they still indicate that the carbonyl iron powder surface is coated with silicon dioxide. Due to the small particle size of SiO2 and the smooth surface of unmodified carbonyl iron powder, which makes uniform deposition difficult, the resulting SiO2 coating layer is relatively thin.

[0052] 6) Analysis of carbonyl iron powder / epoxy resin coating before and after modification: cross-sectional morphology analysis.

[0053] Figure 9 The cross-sectional morphology of SiO2-coated carbonyl iron powder after adding epoxy resin. Figure 9 In (a) and (b), the modified CIP@SiO2 content is 0.50% and 0.75% of the epoxy resin mass, respectively. The modified carbonyl iron powder coating has a relatively smooth surface, a tight bond between the coating and the substrate, and no gaps at the interface, such as... Figure 9As shown, the epoxy resin coating tightly fills the pores on the substrate surface, enhancing the adhesion strength between the coating and the substrate. The magnified cross-sectional morphology reveals no clear boundary between CIP@SiO2 and the epoxy resin, indicating uniform dispersion and dense bonding. The interwoven microstructure effectively increases the interfacial contact area, improves the bonding strength between the coating and the substrate, and enhances the corrosion resistance of the SiO2 carbonyl iron powder / epoxy resin composite material.

[0054] 7) Analysis of carbonyl iron powder / epoxy resin coating before and after modification: open circuit potential diagram analysis.

[0055] Figure 10 To obtain the open circuit potential (OCP) diagrams of carbonyl iron powder before and after modification, the sample to be tested must first be immersed in an electrolyte solution containing 3.5 wt.% NaCl, and the test is conducted in the range of -0.6 V to 0.1 V. Analyzing the magnitude of the open circuit potential can reflect the corrosion resistance of the material to a certain extent.

[0056] As shown in the figure, when the test duration is 600s, the potentials of samples CIP-0.50% are -0.55V, CIP-0.75% are -0.58V, CIP-1.00% are -0.56V, CIP@SiO2-0.50% are -0.37V, CIP@SiO2-0.75% are -0.57V, and CIP@SiO2-1.00% are 0.06V. As time progresses, the highest open-circuit potential for CIP@SiO2-1.00% indicates a lower thermodynamic tendency to corrosion and better corrosion resistance. Conversely, the lowest open-circuit potential for CIP-0.75% indicates weaker corrosion resistance.

[0057] 8) Analysis of carbonyl iron powder / epoxy resin coating before and after modification: impedance spectroscopy analysis.

[0058] Electrochemical impedance spectroscopy (EIS) is an effective electrochemical test for analyzing kinetics and electrode reactions. It can accurately reflect the original information of a sample and perform characteristic analysis on metal surface changes and corrosion levels. The Nyquist curve consists of real and imaginary parts, such as... Figure 11 As shown. Corrosion performance is typically represented by the radius of the capacitance arc curve. Figure 11It can be seen that the capacitance arc radii of CIP-0.50%, CIP-0.75%, and CIP-1.00% are relatively small, while the capacitance arc radii of CIP@SiO2-0.50%, CIP@SiO2-0.75%, and CIP@SiO2-1.00% are significantly larger, with the largest capacitance arc radius observed at a CIP@SiO2 addition of 1.00%, indicating a slower corrosion rate and superior corrosion resistance. Furthermore, the complex impedance modulus |Z| in the Bode plot also describes corrosion resistance; a larger |Z| indicates better corrosion resistance. Figure 11 As shown, the impedance amplitude |Z| of samples CIP-0.50%, CIP-0.75%, CIP-1.00%, CIP@SiO2-0.50%, CIP@SiO2-0.75%, and CIP@SiO2-1.00% at a low frequency of 0.01Hz is 1.5 × 10⁻⁶. 4 Ω·cm 2 4.6×10 4 Ω·cm 2 6.3×10 4 Ω·cm 2 4.5×10 4 Ω·cm 2 6.8×10 3 Ω·cm 2 7.6×10 5 Ω·cm 2 Therefore, the impedance of CIP@SiO2-1.00% is increased by 7.0 × 10⁻⁶ compared to CIP-1.00%. 5 Ω·cm 2 Therefore, it can be concluded that the modified carbonyl iron powder has better corrosion resistance.

[0059] 9) Analysis of carbonyl iron powder / epoxy resin coating before and after modification: polarization curve analysis.

[0060] Figure 12 Table 4 shows the polarization curves of carbonyl iron powder before and after modification. Table 4 shows the current density and corrosion potential after fitting the electrochemical polarization curves of the samples. The ECIP-1.00% sample... corr The value is -0.609V (SCE), while the E of CIP@SiO2 is -1.00%. corr The value is -0.255V (SCE). Therefore, the modified carbonyl iron powder E corr The voltage value is approximately 0.35V (SCE) higher than that of the unmodified product, making CIP@SiO2-1.00% less susceptible to corrosion. The Ig of CIP@SiO2-1.00%... corr The value is 2.1510 -8 A / cm 2 The value less than CIP-1.00% is 4.6010.-6 A / cm 2 Corrosion current density (I) corr The corrosion rate is used as a key indicator to evaluate the corrosion resistance of materials. The surface corrosion rate of CIP@SiO2-1.00% is smaller, indicating that the corrosion resistance of CIP@SiO2-1.00% is better than that of CIP-1.00%.

[0061] Experimental results show that the carbonyl iron powder / epoxy resin coating coated with silica exhibits superior corrosion resistance compared to the epoxy resin coating without SiO2 coating. Furthermore, the corrosion potential is highest and the corrosion current density is lowest when the CIP@SiO2 content is 1.00%, indicating that the slower the corrosion rate, the more difficult the substrate is to corrode.

[0062] Table 4. Fitting results of electrochemical polarization curves of samples ; In summary, the electrochemical tests show that a protective film of SiO2 and epoxy resin is formed on the CIP surface. The micron-sized SiO2 can fill the air bubbles generated by the epoxy resin during stirring, preventing the penetration of corrosive media. The cured epoxy resin has a network structure that coats the composite material, which can prevent direct contact between the corrosive solution and the substrate, slow down electron transfer, and enhance the corrosion resistance of the coating.

[0063] Overall conclusion: (1) In thermogravimetric analysis, unmodified carbonyl iron powder began to oxidize and increase in weight at 200℃, while carbonyl iron powder coated with silica showed a slow increase in weight only at 300℃ and a rapid increase at 500℃. The initial oxidation temperature of carbonyl iron powder before and after modification was 50℃ higher than that of the original sample, indicating that the modified carbonyl iron powder effectively enhanced the antioxidant properties.

[0064] (2) In the microstructure and phase characterization of carbonyl iron powder, the carbonyl iron powder prepared by the improved Stober method has a coarser and denser microstructure particles. The peaks of Si and O elements can be clearly seen from the energy spectrum, indicating that the carbonyl iron powder modified by the Stober method is coated with silicon dioxide.

[0065] (3) Electrochemical parameter results showed that CIP@SiO2-5mL outperformed CIP in open-circuit potential, EIS test, and Tafel test. This indicates that carbonyl iron powder coated with silica has superior corrosion resistance compared to the original carbonyl iron powder. In the open-circuit potential analysis of CIP@SiO2, the voltages of CIP@SiO2-1.00% and CIP-1.00% remained at 0.06V and -0.56V respectively within the test time range. The modified carbonyl iron powder with an addition of 1.00% showed a more positive potential than the unmodified powder, indicating that it is more difficult to corrode. In the Nyquist plot, the radius of the capacitive arc of the silica-coated carbonyl iron powder was larger than that of the original carbonyl iron powder. In the Bode plot, the impedance value of CIP-1.00% at a low frequency of 0.01Hz was 3.2×10⁻⁶. 5 Ωcm 2 The impedance of CIP@SiO2-1.00% is 7.6 × 10⁻⁶. 5 Ωcm 2 Compared to the CIP-1.00% sample (4.4 × 10⁻⁶), 5 Ωcm 2 This indicates that the modified carbonyl iron powder exhibits significantly improved corrosion resistance. In the Tafel curve, the corrosion potential of the sample with a CIP of -1.00% is -0.609V (SCE), and the corrosion current density is 4.60 x 10⁻⁶. -6 A / cm 2 The corrosion potential of the modified CIP@SiO2-1.00% is about 0.13V (SCE) higher than that of CIP-1.00% carbonyl iron powder, and the corrosion current density is also lower. This indicates that the modified carbonyl iron powder has a slower corrosion rate and better corrosion resistance than the unmodified carbonyl iron powder with an addition of 1.00%.

[0066] The above are merely a few preferred embodiments of the present invention, described in a relatively specific and detailed manner, but they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention.

Claims

1. A silica-modified carbonyl iron powder, characterized in that, The carbonyl iron powder forms the core, and its surface is coated with a silicon dioxide layer to form a core-shell structure. The silicon dioxide layer is formed by hydrolysis and condensation on the surface of the carbonyl iron powder using a modified Stober method with tetraethyl orthosilicate as the silicon source and ammonia water as the catalysis. The presence of the silicon dioxide layer ensures that the initial oxidation temperature of the modified carbonyl iron powder is not lower than 300°C, which is at least 50°C higher than that of the unmodified carbonyl iron powder.

2. The silica-modified carbonyl iron powder according to claim 1, characterized in that, The particle size range of the carbonyl iron powder is 1~6μm.

3. The silica-modified carbonyl iron powder according to claim 1, characterized in that, The thickness of the silicon dioxide layer is in the nanometer range, and the surface roughness of the carbonyl iron powder increases significantly after coating.

4. The method for preparing silica-modified carbonyl iron powder according to any one of claims 1-3, characterized in that, Includes the following steps: (1) Dispersion: Weigh 8 parts by weight of carbonyl iron powder and add it to 160-200 parts by volume of deionized water to form a preliminary suspension; (2) Mixed catalysis: Mix 1 volume part of ammonia water with 40-60 volume parts of anhydrous ethanol to obtain a catalytic solution; mix the catalytic solution with the preliminary suspension from step (1), and treat with ultrasonic vibration for 5-15 minutes to obtain a uniformly dispersed carbonyl iron powder suspension. (3) Coating reaction: Place the suspension obtained in step (2) in a constant temperature water bath at 35±2℃, and slowly add 4-6 volume parts of tetraethyl orthosilicate under continuous stirring. Control the stirring rate to 250-300 r / min and the reaction time to 3-4 hours. (4) Post-processing: After the reaction is completed, the reaction product is vacuum filtered to achieve solid-liquid separation, and the obtained solid product is washed 3-5 times alternately with deionized water and anhydrous ethanol; finally, the washed product is dried in a vacuum drying oven at 75-85℃ for 2-3 hours to obtain the silica-modified carbonyl iron powder.

5. The preparation method according to claim 4, characterized in that, The ultrasonic oscillation time in step (2) is 10 minutes.

6. The preparation method according to claim 4, characterized in that, The amount of tetraethyl orthosilicate added in step (3) is 5 parts by volume.

7. A corrosion-resistant composite coating, characterized in that, It consists of an epoxy resin matrix and carbonyl iron powder modified with silica as described in any one of claims 1-3 dispersed therein.

8. The anti-corrosion composite coating according to claim 7, characterized in that, The silica-modified carbonyl iron powder is present in the epoxy resin matrix at a mass percentage of 0.1% to 2.0%.

9. The anti-corrosion composite coating according to claim 8, characterized in that, The silica-modified carbonyl iron powder constitutes 1.00% of the epoxy resin matrix by mass; the low-frequency impedance modulus of this coating in a 3.5 wt.% NaCl solution is not less than 7.0 × 10⁻⁶. 5 Ω·cm 2 The corrosion current density is not higher than 2.15 × 10⁻⁶. -8 A / cm 2 .

10. The method for preparing the anti-corrosion composite coating as described in claim 7, characterized in that, Includes the following steps: Mix the specified mass percentage of silica-modified carbonyl iron powder with epoxy resin A, and disperse it for 15-25 minutes at a rate of 10000-15000 r / min using an ultrasonic disperser. Add the appropriate proportion of epoxy resin B glue, and mechanically stir for 10-20 minutes to make the mixture uniform; Place the mixture in a vacuum environment to remove air bubbles for 5-15 minutes; The degassed mixture is coated onto the surface of the pretreated metal substrate and cured at room temperature for no less than 12 hours to form the anti-corrosion composite coating.

Citation Information

Cited By

  • Magnetic control semi-filled microsphere flexible sensor and preparation method thereof

    CN121558212A